Quick Response Code for Inventory System Development (Case study : Accounting Unit At Ujung Pandang State Polytechnic) - Hayani, Hayani; Raharjo, Muh. Fajri; Tungadi, Eddy (Politeknik Negeri Ujung Pandang, 2022)
QR stands for Quick Response, which is in accordance with its purpose is to convey information quickly and get a fast response as well. In contrast to barcodes which are only able to store information horizontally, QR codes are able to store information both horizontally and vertically. So that automatically QR codes have the ability to store more data than barcodes. QR codes can be used in the inventory system at the State Polytechnic of Ujung Padang to make it easier to read inventory data.In this study, the author will create an inventory system using a QR Code. The inventory system will be made online so that it can make it easier for admins and staff to process data and present information. This system is made in PHP and usesÂ MySQL database for data storage, while the QR code is created using the Ciqrcode library. While in reading the QR code on the android application using the Zxing library. The inventory system built can make it easier to process inventory data and present information to the Accounting Unit at State Polytechnic of Ujung Padang.